The 9/11 terror attacks : Odysseys - Bodden, Valerie (Mankato, Minnesota Creative Education, 2016)
"A look at the causes and global effects of the terror attacks carried out in the United States on September 11, 2001, which set in motion the events of the War on Terror and hunt for al Qaeda"--
September 11, 2001 -- A small world -- Attack on America -- Never forget -- Islamic extremists -- Osama bin Laden -- The Mujahideen -- No evacuation -- Emergency responders -- Passenger assistance -- Saved by a stairwell -- Everyday heroes -- Zacarias Moussaoui -- Invading Iraq.
1340L
Keywords: September 11 Terrorist Attacks -- 2001; Terrorism -- United States; War on Terrorism -- 2001-2009; United States; Juvenile works